Use of manure for development of papaya seedlings colonized with mycorrhizal fungi - Trindade, Aldo Vilar; Faria, Nelita Gonçalves; Almeida, Florício Pinto de (Pesquisa Agropecuaria Brasileira, 2000)
This research tested the use of manure as part of the substrate for production of papaya (Carica papaya L.) seedlings enabling the establishment and expression of mycorrhizal symbiosis. Five levels of manure were tested: 0, 5, 10, 20 and 30% with or without inoculation of Glomus etunicatum. Results obtained after 50 days of culture showed that plants have higher growth at 20% and 30% of manure in the soil; use of P and K have no addition effect on plant growth; inoculation of G. etunicatum is efficient for development of plants in soils with up to 10% of manure; all levels of manure used permit the establishment of the fungi on the roots but with a decreasing effect at the highest levels of manure; the combination of 10% of manure and inoculation of AM fungi promote healthy plants without symptoms of nutrient deficiency and suitable for transplanting to the field.